OrBI – A Hands-free Virtual Reality User Interface for Mobile Devices - Rozatto, Paulo Victor de Magalhães; Oliveira, André Luiz Cunha de; Silva, Rodrigo Luis de Souza da (Journal of Mobile Multimedia, 2022)
The purpose of this paper is to present OrBI, a framework for developing hands-free user interfaces for interacting with low-cost Virtual Reality systems through mobile devices. The proposed implementation was developed and used in various Virtual Reality apps. To assess OrBI’s precision and ease to use, we submit the framework to a quantitative and qualitative evaluation. The findings indicate that the proposed interface model is easy to use and have a suitable precision. The findings also showed that the framework might be challenging for older people to use and, in some cases, tiresome.